Analisys of Students' Understanding in Concept of Biodiversity Using Two Tier Multiple Choice Test in SMAN 1 Rupat Utara - Amalia Suci Erliza; Armen Armen; Relsas Yogica; Ganda Hijrah Selaras (Universitas Negeri Padang, 2020)
Understanding of concepts must be possessed by each student in order to get good learning outcomes and be able to apply concepts in daily life. Some of the biology's theories that is abstract and discusses variations of living things make it difficult for students to understand the concept, may also affect the test scores and it's not compatiblefor students to apply in their daily life. This study aims to determine the level of understanding of students about the concept of biodiversity material. This study was a descriptive study conducted at SMAN 1 Rupat Utara. The population of this research is MIPA students in 10th grade. The sample of this study took everymember of the population as many as 60 people. The sampling technique that used was a total sampling technique. The data used are primary data that obtained through research instruments such as two-tier multiple choice tests and analyzed quantitatively.Based on the results of the study, it obtained the level of the students'understanding in class X MIPA SMAN 1 Rupat Utara on biodiversity material that has understood the conceptis25.7%, 8.59% is misconception, and those who do not understand the concept is 65.8%.